Homiletic Elements of the Orthodox Iconography - Beldiman, Nicușor (Forum Theologicum Sardicense, 2025)
Homiletic Elements of the Orthodox Iconography. Fr. Beldiman presents an intriguing methodology for theological research in the field of Orthodox liturgical art, specifically icons. His approach integrates Homiletics with visual Christian art into a cohesive whole, combining it with Orthodox Soteriology.